Demographic analysis of Tamaulipas - Izacara Palacios, Simón Pedro (Libros UAT, 2018)
Demography is a social science that measures and explains the events and processes that determine the formation, conservation, renewal, growth and disappearance of human populations through births, deaths and migratory movements. Demographic analysis is a discipline that is particularly arid for students of social sciences, since it involves the use of statistical-mathematical procedures whose appearance is complex and obscure. However, the types of measurement and analysis used by the demographer are basic and fundamental in social research. This work, which takes as an example the population of Tamaulipas, aims to bring demographic analysis techniques to those students of social sciences, both undergraduate and postgraduate, who lack advanced knowledge of mathematical demography, but who have the need to address this discipline in their research. That is why aspects such as the standardization of a gross rate, the construction of a life table, the projection of a population, etc., are simplified and explained in a thorough manner to facilitate their understanding.